Reciprocal, Temporal Expression of SpeA and SpeB by Invasive M1T1 Group A Streptococcal Isolates In Vivo - Kazmi, Shahana U. (American Society for Microbiology, 2001)
The streptococcal pyrogenic exotoxins (Spes) play a central role in the pathogenesis of invasive group A streptococcal (GAS) infections. The majority of recent invasive GAS infections have been caused by an M1T1 strain that harbors the genes for several streptococcal superantigens, including speA, speB, speF, speG, and smeZ. However, considerable variation in the expression of Spe proteins among clonal M1 isolates has been found, and many of the speA-positive M1 strains do not produce detectable amounts of SpeA in vitro. This study was designed to test the hypothesis that speA gene expression can be induced in vivo. A mouse infection chamber model that allows sequential sampling of GAS isolates at various time points postinfection was developed and used to monitor the kinetics of Spe production in vivo. Micropore Teflon diffusion chambers were implanted subcutaneously in BALB/c mice, and after 3 weeks the pores became sealed with connective tissue and sterile fluid containing a white blood cell infiltrate accumulated inside the infection chambers. Representative clonal M1T1 isolates expressing no detectable SpeA were inoculated into the implanted chambers, and the expression of SpeA in the aspirated aliquots of the chamber fluid was analyzed on successive days postinfection. Expression of SpeA was detected in the chamber fluid as early as days 3 to 5 postinfection in most animals, with a significant increase in expression by day 7 in all infected mice. Isolates recovered from the chamber and grown in vitro continued to produce SpeA even after 21 passages in vitro, suggesting stable switch on of the speA gene. A temporal relation between the upregulation of SpeA expression and the downregulation of SpeB expression was observed in vivo. These data suggest that in vivo host and/or environmental signals induced speA gene expression and suppressed speB gene expression. This underscores the role of the host-pathogen interaction in regulating the expression of streptococcal virulence factors in vivo. The model described here should facilitate such studies.